Perancangan Dashboard Detail Downtime Oee Untuk Visualisasi dan Analisis Pada PT Xy - Imron Abdul Rouf; Sumiati Royan (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Industry is an economic activity that processes raw materials, raw materials, semi-finished goods, and/or finished goods into goods with higher value. Industrial revolution 4.0 is often also called the cyber physical system. PT XY to run its business has a system, namely Management System (MS). MS cannot be separated from information technology to support KPI achievement. One of the information technologies that needs to be applied to the production department is OEE Downtime Details as a Realtime production report. currently has a system that is not yet effective in OEE KPIs, especially in Downtime Details. The method that can be used to complete analysis related to this problem is the Pureshare Method which displays quantitative data to provide motivation and suitability for business and technology goals. The results obtained from this research are that creating a dashboard can increase the effectiveness of data input and the data can be standardized so that the data is more valid. Suggestions for further research require evaluation regarding the development of information that will be presented on the dashboard.